Outcomes Associated With Medications for Opioid Use Disorder Among Persons Hospitalized for Infective Endocarditis. (21st January 2020) - Barocas, Joshua A; Morgan, Jake R; Wang, Jianing; McLoone, Dylan; Wurcel, Alysse; Stein, Michael D
Abstract: Background: Endocarditis, once predominately found in older adults, is increasingly common among younger persons who inject drugs. Untreated opioid use disorder (OUD) complicates endocarditis management. We aimed to determine if rates of overdose and rehospitalization differ between persons with OUD with endocarditis who are initiated on medications for OUD (MOUDs) within 30 days of hospital discharge and those who are not. Methods: We performed a retrospective cohort study using a large commercial health insurance claims database of persons ≥18 years between July 1, 2010, and June 30, 2016. Primary outcomes included opioid-related overdoses and 1-year all-cause rehospitalization. We calculated incidence rates for the primary outcomes and developed Cox hazards models to predict time from discharge to each primary outcome as a function of receipt of MOUDs. Results: The cohort included 768 individuals (mean age 39 years, 51% male). Only 5.7% of people received MOUDs in the 30 days following hospitalization. The opioid-related overdose rate among those who did receive MOUDs in the 30 days following hospitalization was lower than among those who did not (5.8 per 100 person-years [95% confidence interval [CI], 5.1–6.4] vs 7.3 per 100-person years [95% CI, 7.1–7.5], respectively). The rate of 1-year rehospitalization among those who received MOUDs was also lower than those who did not (162.0 per 100 person-years [95% CI, 157.4–166.6] vs 255.4 per 100 person-years [95% CI, 254.0–256.8], respectively). In the Cox hazards models, the receipt of MOUDs was not associated with either of the outcomes. Conclusions: MOUD receipt following endocarditis may improve important health-related outcomes in commercially insured persons with OUD. Abstract : Health outcomes were improved when people with opioid use disorder who were hospitalized with endocarditis received medications for opioid use disorder (MOUDs). Compared with no MOUDs, receipt within 30 days of hospitalization was associated with reductions in overdose and rehospitalization.